2019
DOI: 10.12659/aot.916649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretransplant Dialysis Modality on Outcomes After Simultaneous Pancreas-Kidney Transplantation

Abstract: Background:Pretransplant dialysis modality may affect outcome after simultaneous pancreas-kidney transplantation (SPKT), and it has been suspected that peritoneal dialysis (PD) is associated with more postoperative complications compared to hemodialysis (HD). The aim of this study was to evaluate whether pretransplant dialysis modality affects the risk for postoperative complications in SPKT recipients. Material/Methods:This was a retrospective longitudinal cohort study of all patients undergoing SPKT from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Simultaneous pancreas-kidney transplantation (SPK) has established its importance as endocrine replacement therapy for patients with type 1 diabetes and end-stage kidney disease 1,2 . However, severe postoperative complications still negatively affect both short-and long-term outcomes [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous pancreas-kidney transplantation (SPK) has established its importance as endocrine replacement therapy for patients with type 1 diabetes and end-stage kidney disease 1,2 . However, severe postoperative complications still negatively affect both short-and long-term outcomes [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, severe postoperative complications still negatively affect both short-and long-term outcomes. [3][4][5] Majority of the complications are related to the pancreas allograft and include hemorrhage, vascular thrombosis,…”
mentioning
confidence: 99%
“…[20]. In contrast to that, other studies reported no difference in surgical outcome between HD and PD patients after SPKT [21][22][23][24].…”
Section: Impact Of Demographical and Clinical Variablesmentioning
confidence: 87%
“…Martins et al reported a significantly higher rate of pancreas loss due to infection among PD patients after SPKT (HD: 3.4% versus PD: 12.8%; P = 0.042), whereas ten out of 39 (25.6%) PD patients had peritonitis in their past [20]. By contrast, other studies have reported no difference in surgical outcome between HD and PD patients after SPKT [21][22][23][24]. Our analysis could not reveal significant differences in intraabdominal infection rates after SPKT between the two groups, and there was no correlation between the incidence of pre-transplant peritonitis and post-transplant intra-abdominal infection.…”
Section: Discussionmentioning
confidence: 97%